Development and application of humanistic logistics models for optimizing location-allocation problem solutions to volcanic eruption disaster (Case study: Volcanic eruption of Mount Merapi, Indonesia). Issue 1 (1st January 2017) - Prabowo, Aditya Respati; Dwicahyani, Anindya Rachma; Jauhari, Wakhid Ahmad; Aisyati, Azizah; Laksono, Pringgo Widyo
Abstract: Logistics distribution in the event of natural disasters, such as volcanic eruptions, earthquakes and floods, is an important matter that needs attention of both government and society. The distribution of logistics in many disaster-prone countries, including Indonesia, is poorly planned and managed. Therefore, various problems arise, such as low efficiency and effectiveness of delivery and poor cost-effective flow. This study developed location-allocation models for distribution and evacuation of refugees and logistics. The investigation was conducted by determining the characteristics of the disaster management system of volcanic eruption in Mount Merapi, Indonesia. The mathematical model was built and a set of solution procedure was proposed to solve the problem. The objective of the model is to minimize total costs of the system and determine the optimal solutions at the three alert-levels, which are alert phase, danger phase and post-disaster phase. The results were discussed and models were analyzed to give several managerial insights regarding the model's optimal solution. Based on the results, the proposed models are proven to give more effective solutions at lower costs. The usage of each evacuation shelter can be utilized to its maximum level. Therefore, it allows minimum waste of capacity as well as costs related to evacuation and distribution.